A Novel UDP-Glycosyltransferase of Rhodiola crenulata Converts Tyrosol to Specifically Produce Icariside D2. (20th June 2018) - Liao, Zhihua; Qiu, Fei; Zeng, Junlan; Gu, Li; Wang, Bangjun; Lan, Xiaozhong; Chen, Min
Abstract : Rhodiola crenulata is a Tibetan native herbal plant belonging to the family of Crassulaceae, which produces the pharmaceutical icariside D2 with the activities of inhibiting angiotensin-converting enzyme and killing leukemia cancer cells. In this study, we functionally characterized a novel UDP-glycosyltransferase (RcUGT1) that converted tyrosol to specifically produce icariside D2 from R . crenulata at molecular and biochemical levels. RcUGT1 was highly expressed in flowers and roots, while the icariside D2 content was much higher in stems than that in other organs, suggesting the potential translocation of icariside D2 from flowers and roots to stems. The high production of icariside D2 in stems provided a reasonable suggestion to farmers to harvest stems instead of roots for icariside D2 production. Enzymatic assays of recombinant RcUGT1 indicated that it converted tyrosol to specifically form icariside D2, with the values of K m 0.97±0.10 mM, V max 286±8.26 pKat/mg, K cat 0.01552 s −1, and K cat/ K m 159.55 s −1 M −1 . Functional identification of RcUGT1 facilitated the icariside D2 production through metabolic engineering in plants or synthetic biology in microbes.